Progesterone receptors: a key for neuroprotection in experimental stroke - Liu, Ailing (2012)
Progesterone receptors (PR) are expressed throughout the brain. However, their functional significance remains understudied. Here we report a novel role of PR as crucial mediators of neuroprotection using a model of transient middle cerebral artery occlusion and PR knockout mice. Six hours after ischemia, we observed a rapid increase in progesterone and 5-dihydroprogesterone, the endogenous PR ligands, a process that may be a part of the natural neuroprotective mechanisms. PR deficiency, and even haploinsufficiency, increases the susceptibility of the brain to stroke damage. Within a time window of 24 h, PR-dependent signaling of endogenous brain progesterone limits the extent of tissue damage and the impairment of motor functions. Longer-term improvement requires additional treatment with exogenous progesterone and is also PR dependent. The potent and selective PR agonist Nestorone is also effective. In contrast to progesterone, levels of the neurosteroid allopregnanolone, which modulates -aminobutyric acid type A receptors, did not increase after stroke, but its administration protected both wild-type and PR-deficient mice against ischemic damage. These results show that 1) PR are linked to signaling pathways that influence susceptibility to stroke, and 2) PR are direct key targets for both endogenous neuroprotection and for therapeutic strategies after stroke, and they suggest a novel indication for synthetic progestins already validated for contraception. Although allopregnanolone may not be an endogenous neuroprotective agent, its administration protects the brain against ischemicdamageby signaling mechanisms not involving PR. Collectively, our data clarify the relative roles of PR and allopregnanolone in neuroprotection after stroke.